Comparative analysis of low-temperature PVD-based TiN nano-thin-film-coated and -uncoated TNMG inserts in dry machining. (17th February 2020) - Zafar, Muhammad Qasim; Uddin, Ghulam Moeen; Asim, Muhammad; Khan, Awais Ahmed; Tahir, Zia-Ur-Rehman; Hayat, Nasir; Ghufran, Muhammad; Jawad, Muhammad
ABSTRACT: Titanium nitride (TiN) is a hard-ceramic material having excellent wear and corrosion resistance properties. In this study, TiN coating has been deposited on carbide cutting inserts by a low-temperature cathodic arc phsical vapor deposition (PVD) system. Comparative analysis of machining performance, based on tool life and work piece surface roughness, has been done between the TiN-coated carbide cutting inserts and uncoated carbide cutting inserts in dry machining of medium carbon AISI 1045 steel. Design of experiments (DOE) technique along with response surface regression has been used for the optimization of machining parameters. The most significant factor affecting the surface roughness of the work piece in dry machining was found to be the feed rate. TiN-coated carbide cutting inserts showed 15% improvement in the surface roughness of work piece and 60% improvement in tool life as compared to uncoated carbide cutting inserts.